New parents and driver safety: What's sleep got to do with it? A systematic review. (August 2022) - Sprajcer, Madeline; Crowther, Meagan E.; Vincent, Grace E.; Thomas, Matthew J.W.; Gupta, Charlotte C.; Kahn, Michal; Ferguson, Sally A.
Highlights: New parents are likely to experience sleep loss due to childcare responsibilities. A systematic review was performed to understand the relationship between sleep and driver fatigue in new parents. Synthesis of available evidence suggests that new parents are at risk of fatigued driving. A research agenda is proposed to address the limitations of this field of research. Abstract: Fatigue-related motor vehicle crashes are common worldwide and have been addressed by a range of road safety campaigns. These campaigns are typically directed towards at-risk groups (e.g., heavy vehicle drivers), who may be likely to experience fatigue resulting from reduced or disrupted sleep opportunities. Another population likely to experience sleep loss and disruption is new parents. The sleep of new parents is likely to be significantly disrupted by childcare responsibilities. As such, new parents may also be likely to experience fatigue while driving. A systematic review of five databases (PubMed, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, EMBASE, and the Cochrane Central Register of Controlled Trials) was performed to identify what research is currently available on sleep, fatigue, and driving in new parents. A total of twelve documents were included in this review. A synthesis of findings suggests new parents are at risk of fatigued driving – though the amount and quality of evidence available is limited. A research agenda is proposed to address the limitations of this field of research.